Further evidence on the link between firm's control mechanisms and firm financial performance: Sultanate of Oman - Ahmed, Essia Ries; Alabdullah, Tariq Tawfeeq Yousif; Muhammad Shabir, Shaharudin; Putri, Eskasari (Penerbit Universiti Malaysia Pahang, 2020)
Based on the agency theory perspective and its corporate governance problem, the current study investigated how control mechanisms affect firm financial performance with a special concentrate on the role of the audit committee on the enhancement of firm financial performance. The empirical findings of this study based on the listed firms in the Sultanate of Oman revealed that the control mechanisms, including committee size and board independence, positively enhance financial performance represented by ROEand therefore this leads to encouraging firms to focus on such mechanisms. By contrast, audit size, board size and board independence are totally not motivated to engage with financial performance due to the insignificant link with ROA. On the other hand,a negative correlation has been found between a board meeting and financial performance represented by ROE. The practical evidence of the implicationsby the current study found that for improvement of firm financial performance; that even though if mostof the GCC governments recently have focused on corporate social responsibility because largely voluntary nature of corporate social responsibility, they should focus of the control mechanisms that suggested by the current study to play a significant rolefor enhancing firm financial performance.